Catching wildfowl by artificial light - Dennis, Roy H (Wildfowl, 1966)
At Fair Isle Bird Observatory we use an assortment of methods for catching birds to ring. The majority of our catch each year are either passerines trapped in permanent Heligoland traps, small wire traps and mist-nets, or Fulmars, Shags, auks and gulls, ringed on the cliffs. Since 1959 we have been catching a variety of species by the use of artificial light at night. We have been particularly interested in those species which do not usually enter our normal traps, including wildfowl, waders and wintering gulls. We have so far caught and ringed by the use of artificial light about 630 birds of 51 species. In 1965, we caught 166 birds of 28 species by this method alone.